Impact of the society’s perception on teachers’ professionalism - Arifah Fauziah; Maksim Kim; Mulunesh Aye; Venant Hakizimana; Ju Hur (Journal of Education and Learning (EduLearn), 2021)
An effective teaching contributes to the students’ performance and this depends on qualified-trained teachers, school administration, parents and conducive environment for teaching and learning. It is proven that students are more successful in their academic achievements, in the societies where teachers perceive their profession as their job. This paper explores the impact of the society’s perception on teachers’ professionalism. The method employed in this paper is qualitative by using interview technique and used audio-recorded to ensure a complete transcript. The result indicated that in some developing countries including Cameroon, Kenya and Fiji has various reasons for their job. Teaching profession was affected by how the society considers teachers whereby they are perceived as disadvantaged population who cannot fully take part in the social and economic activities due to the fact that their salary is very low compared other public servants. This low salary and loss of respect of teachers by the society lead to the job dissatisfaction and made the teaching profession as a transitional job before waiting to move to another different professional field.